Evidence for dispersal syndromes in freshwater fishes. Issue 1871 (31st January 2018) - Comte, Lise; Olden, Julian D.
Abstract : Dispersal is a fundamental process defining the distribution of organisms and has long been a topic of inquiry in ecology and evolution. Emerging research points to an interdependency of dispersal with a diverse suite of traits in terrestrial organisms, however the extent to which such dispersal syndromes exist in freshwater species remains uncertain. Here, we test whether dispersal in freshwater fishes (1) is a fixed property of species, and (2) correlates with life-history, morphological, ecological and behavioural traits, using a global dataset of dispersal distances collected from the literature encompassing 116 riverine species and 196 locations. Our meta-analysis revealed a high degree of repeatability and heritability in the dispersal estimates and strong associations with traits related to life-history strategies, energy allocation to reproduction, ecological specialization and swimming skills. Together, these results demonstrate that similar to terrestrial organisms, the multi-dimensional nature of dispersal syndromes in freshwater species offer opportunities for the development of a unifying paradigm of movement ecology that transcend taxonomic and biogeographical realms. The high explanatory power of the models also suggests that trait-based and phylogenetic approaches hold considerable promises to inform conservation efforts in a rapidly changing world.